Association between Soluble Transferrin Receptor with Central Obesity - Muh Taufiq; Liong Boy Kurniawan; Mansyur Arif (Universitas STRADA Indonesia, 2022)
Subclinical chronic inflammation in central obesity theoretically leads to hepcidin synthesis in large amount, which inhibits iron absorption and inhibits the release of iron stores from macrophages. This subsequently leads to an increase in soluble transferrin receptor (sTfR) levels due to inadequate cellular iron. This study aims to determine the association between sTfR levels with central obesity. The study design was cross sectional with 75 subjects selected purposively. The sTfR level was determined using ELISA technique. Descriptive statistical method and bivariate analysis were employed to determine the association between these variables. The results showed that there was a significant difference in terms of sTfR levels of central obese individuals with those of non-central obese one. In line with this finding, waist circumference also exhibited a positive correlation with sTfR levels. In addition, we found no systematic relationship between gender and age with respect to sTfR levels. From these results, it was concluded that the sTfR levels were higher in subjects with central obesity compared to non-central obesity, and the greater the waist circumference, the higher the sTfR levels.